2010
DOI: 10.1109/tns.2010.2044892
|View full text |Cite
|
Sign up to set email alerts
|

A Four-Layer DOI Detector With a Relative Offset for Use in an Animal PET System

Abstract: For animal PET systems to achieve high sensitivity without adversely affecting spatial resolution, they must have the ability to measure depth-of-interaction (DOI). In this paper, we propose a novel four-layer PET system, and present the performances of modules built to verify the concept of the system. Each layer in the four-layer PET system has a relative offset of half a crystal pitch from other layers. Performances of the four-layer detector were estimated using a GATE Monte Carlo simulation code. The prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 72 publications
(57 citation statements)
references
References 19 publications
1
56
0
Order By: Relevance
“…Several groups have shown that depth-ofinteraction encoding with SiPM is feasible (13). Implementing the depth-of-interaction encoding methods suggested by our group (14,16,32) will also be possible using the SiPM arrays.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Several groups have shown that depth-ofinteraction encoding with SiPM is feasible (13). Implementing the depth-of-interaction encoding methods suggested by our group (14,16,32) will also be possible using the SiPM arrays.…”
Section: Discussionmentioning
confidence: 97%
“…The dead space between the sensitive areas of SiPMs was 2 mm between each column of the SiPM array and 1 mm between each row. Each crystal, with a dimension of 1.5 · 1.5 · 7.0 mm, was optically separated using a grid of an enhanced spectral reflector polymer (3M) with a 0.065-mm thickness (14,16). The pitch between the crystals was 1.65 mm on average, resulting in a packing fraction of 85% for a detector module.…”
Section: Detector Modulementioning
confidence: 99%
“…Most DOI detectors employ light sharing over several photosensors, utilize crystals with varied decay time constant, or deliberately alter light collection/wavelength along a scintillator crystal. [21][22][23][24][25][26][27][28][29] This, inevitably, in most cases slows the rise-time and reduces signal-to-noise ratio of the detector signal, compromising timing performance. 15 It is therefore, extremely challenging to fabricate a high performance TOF detector that also provides fine DOI resolution.…”
Section: Background and Theorymentioning
confidence: 99%
“…high light yield, stopping power, and short decay time). We performed timing measurements on the R9800 using a 4 × 4 × 10 mm 3 LYSO crystal whose properties were almost the same as those of the LSO and found it to have excellent performance in our previous investigations [10,11]. The crystal size used in this study (having a large cross section and short length) allowed the timing resolution to not be affected by the geometry of crystal.…”
Section: Fast Pmts and Lysomentioning
confidence: 90%